Peroral Endoscopic Myotomy with Simultaneous Endoscopic Fundoplication for a patient with achalasia - A. A. Smirnov; S. F. Bagnenko; M. E. Lyubchenko; M. M. Kiriltseva; E. V. Blinov; N. V. Konkina; D. I. Vasilevskiy; A. B. Kargabayeva (Вестник хирургии имени И.И. Грекова)
To treat the patient with Achalasia and prevent the symptoms of gastroesophageal reflux the Peroral Endoscopic Myotomy with Simultaneous Endoscopic Fundoplication was done by the current authors. After performing a myotomy the endoloop was fixated to the stomach and was attached to the muscle of the esophagus by using the endoclips. The endoloop was tightened therefore shaping the cuff. This operation has been technically feasible and no immediate or delayed complications occurred.